Saponins isolated from the Vietnamese sea cucumber Stichopus chloronotus. - Vien, Le Thi; Thao, Nguyen Phuong; Hong Hanh, Tran Thi; Thanh Huong, Phan Thi; Thanh, Nguyen Van; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Thung, Do Cong; Kiem, Phan Van; Kim, Young Ho; Minh, Chau Van (Vietnam Journal of Chemistry, 2015)
Using various chromatographic methods, three triterpene saponins neothyonidioside (1), stichoposide D (2), and holothurin B (3), were isolated from the methanol extract of the sea cucumber Stichopus chloronotus. Their structures were elucidated by 1D and 2D-NMR experiments and comparison of their NMR data with reported values. Compound 1 was isolated from S. chloronotus for the first time.